Lessons on the quality of tuberculosis diagnosis from standardized patients in China, India, Kenya, and South Africa - Benjamin Daniels; Ada Kwan; Madhukar Pai; Jishnu Das (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2019)
Standardized patients (SPs) are people who are recruited locally, trained to make identical scripted clinical presentations, deployed incognito to multiple different health care providers, and debriefed using a structured reporting instrument. The use of SPs has increased dramatically as a method for assessing quality of TB care since it was first validated and used for tuberculosis in 2015. This paper summarizes common findings using 3,086 SP-provider interactions involving tuberculosis across various sampling strata in published studies from India, China, South Africa and Kenya. It then discusses the lessons learned from implementing standardized patients in these diverse settings. First, quality is low: relatively few SPs presenting to a health care provider for the first time were given an appropriate diagnostic test, and most were given unnecessary or inappropriate medication. Second, care takes a wide variety of forms – SPs did not generally receive “wait and see” or “symptomatic” care from providers, but they received a medley of care patterns that included broad-spectrum antibiotics as well as contraindicated quinolone antibiotics and steroids. Third, there is a wide range of estimated quality in each observed sampling stratum: more-qualified providers and higher-level facilities performed better than others in all settings, but in every stratum there were both high- and low-quality providers. Evidence from SP studies paired with medical vignettes has shown that providers of all knowledge levels significantly underperform their demonstrated ability with real patients. Finally, providers showed little response to differences in patient identity, but showed strong responses to differences in case presentation that give some clues as to the reasons for these behaviors. Keywords: Quality of care, Tuberculosis, Standardized patients, Health care providers, Low- and middle-income countries